P103 An audit of patients prescribed PrEP using telephone appointments in a community sexual health centre during the COVID-19 pandemic. (16th June 2022) - Riewer, Madryn; Fernando, Imali
Abstract : Introduction: Our service switched routine PrEP consultations to telephone appointments from May2020 due to the Covid-19 pandemic. We undertook an audit of revised service, on patients first prescribed Emtricitabine/Tenofovir as HIV pre-exposure prophylaxis (PrEP) in August/September2021. Methods: Retrospective review of electronic patient records conducted on first 60 patients attending PrEP start appointment from 02/08/21-22/09/21. Demographics, referral pathway, tests performed, vaccine status and prescription outcome recorded. Results compared to national BHIVA/BASHH and service guidelines. Results: 10 patients excluded: 8 on NHS-PrEP already, 2 failed criteria and did not start PrEP. All 50 patients were cis-men who have sex with men, 14% bisexual. Median age 25-34years (range:16–55+). 93%(26/28) of documented patient ethnicity was white. Self-referrals accounted for 46%(15/33) of documented referral-routes. 25(50%) patients waited ≥2months for appointment. 46 patients prescribed NHS-PrEP met recommended BHIVA/BASHH criteria, 4(8%) failed criteria and to self-source. 36(72%) patients met BHIVA/BASHH guidelines for HIV testing, negative in 4weeks before first appointment(BFA). 73%(24/33) of patients with HIV risk after testing had repeat within 6weeks. In 3months BFA, 45(90%) patients had sexual health screen (SHS) and 26(52%) patients received hepatitis B&C testing. In 4months after, 39%(7/18) repeated hepatitis B, 54%(7/13) hepatitis C tests. 94%(29/31) patients requiring vaccinations agreed to receive. 48(96%) patients had eGFR checked in 6months BFA, no eGFR<60. Discussion: Our service ensures patients meet recommended criteria for NHS-PrEP prescription and undertake renal testing and SHS. Vaccines initiated for most patients in need. Proportion of patients receiving baseline hepatitis B&C testing requires improvement. Patient pathways are being reviewed to ensure testing 2-3weeks BFA.